Biosignal monitoring using wearables: Observations and opportunities. (September 2017) - Athavale, Yashodhan; Krishnan, Sridhar
Abstract : Highlights: A review on selected wearable devices for biosignal monitoring is presented. Discussion on factors involving wearable design for health monitoring applications. Defined a set of criteria for designing practical wearables for biosignal analysis. Abstract: Advances in data acquisition technologies, sensor design, data frameworks, smart device connectivities, Internet-of-things, rising health care costs and public awareness towards a better quality of life, have spurred a boom in development of wearable "health-tech" devices in the smart device market. Tele-monitoring of human body dynamics through activities of daily life has become a popular lifestyle choice for consumers, as it helps them keep track of parameters such as food intake, calories burnt, activity levels, or even calling the nearest health care facility during emergencies. Although these devices give the user an intuitive and interactive interface to track body parameters, their use is still limited when compared to vital body parameters in a clinical context. Through this study we are attempting to investigate the clinical applications of wearable devices for biosignal and disease monitoring. In this review study, we have covered a plethora of challenges and opportunities with respect to wearable device design and the inherent possibilities for biosignal analysis and interpretation. Additionally, we have also attempted a comparison of some vital biosignals obtained from wearables and clinical equivalents, which would be useful in determining specific criteria for designing a clinically relevant wearable device.